Pengembangan Media Wayang Kartun Berbasis Kearifan Lokal Untuk Meningkatkan Berpikir Kritis Siswa Kelas V UPT SD Negeri 188 Gresik - Siti Rohmah; Nurul Agustin (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2025)
This study aims to develop a learning media in the form of cartoon puppets based on local wisdom to enhance critical thinking skills of elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fifth-grade students of UPT SD Negeri 188 Gresik. Instruments included expert validation sheets, teacher and student response questionnaires, and pretest-posttest items. Validation results from content and media experts showed that the developed media is highly feasible, with feasibility percentages of 95% and 97%. The implementation phase revealed an increase in average student scores from 74.5 (pretest) to 88.75 (posttest), and mastery learning improved from 50% to 85%. These findings suggest that cartoon puppet media based on local wisdom is effective in improving students’ critical thinking while instilling cultural values in the learning process. Thus, this media can be considered an innovative alternative for contextual and character-based learning.